Public health and public health ethics - Benatar, Solomon R. (Acta Bioethica, 2003)
Spectacular achievements in the health of individuals have not been matched by equivalent improvement in the health of whole populations. Indeed it is against the background of deterioration in levels of population health in some parts of the world and the emergence and re-emergence of infectious diseases in association with powerful globalizing forces that there has been a recrudescence of interest in ‘Public Health’. Here attention is drawn to the dominant values that have shaped our world, to the differences between broad and narrow definitions of public health, to some values that need to be promoted, and to an ethic of public health that considers both human rights and human needs.